The Effect of Medial Arch Support on Reducing Plantar Fasciitis Pain with Isolated Gastrocnemius Tightness (IGT) in Elementary School Teachers of Tetuko, Masaran - Syaifuddin, Muhammad; Septiani, Anissa Eka (Poltekkes Kemenkes Jakarta I, 2025)
Background: Plantar fasciitis is an inflammatory condition of the plantar fascia that is often triggered by muscle tension, such as Isolated Gastrocnemius Tightness (IGT) causing pain in the heel and arch of the foot. Teachers, the risk of plantar fasciitis increases due to prolonged standing during teaching. The use of medial arch support is expected to reduce tension on muscles and ligaments, reducing pain due to plantar fasciitis with IGT. Aims: To evaluate the effectiveness of using medial arch support in reducing plantar fasciitis pain with IGT. Methods: The research is quantitative using a quasi-experimental one-group pre-test and post-test design. The study was conducted at Tetuko Elementary School. The sample consisted of 37 plantar fasciitis patients with IGT. Pain was measured using VAS before and after 4 weeks of intervention using medial arch support. Results: Wilcoxon Signed Rank Test results showed a decrease in pain of 0.000 (p <0.05). The average pain score before intervention was 5.38, which decreased to 3.11. The mean value of the Silfverskiold Test before intervention was 9.700 after the use of medial arch support increased to 15.350. Conclusion: This study shows that the use of medial arch support significantly reduces plantar fasciitis pain with IGT. The results of the analysis showed a significant reduction in pain based on VAS measurements of 42.19%. In addition, there was a significant increase in the Silfverskiold Test results for IGT of 47.94%, indicating improved flexibility of the gastrocnemius muscle.